Listeria monocytogenes infection differentially affects expression of ligands for NK cells and NK cell responses, depending on the cell type infected. Issue 3 (17th January 2018) - Shegarfi, Hamid; Rolstad, Bent; Kane, Kevin P; Nestvold, Janne
Abstract: The pivotal role of NK cells in viral infection is extensively studied, whereas the role of NK cells in bacterial infection has been poorly investigated. Here, we have examined how Listeria monocytogenes (LM) affects expression of ligands for NK cell receptors and subsequent NK cell responses, depending on the type of cell infected. LM infected rat cell lines derived from different tissues were coincubated with splenic NK cells, and NK cell proliferation and IFN-γ production were measured. In addition, expression of ligands for the NK cell receptors Ly49 and NK cell receptor protein 1 (NKR-P1), MHC class I and C-type lectin-related molecules, respectively, was assessed. Infected pleural R2 cells, but not epithelium-derived colon carcinoma cell line CC531 cells, induced proliferation of NK cells. Reporter cells expressing the inhibitory NKR-P1G receptor or the activating NKR-P1F receptor were less stimulated under incubation with infected CC531 cells versus uninfected CC531 controls, suggesting that the ligand(s) in question were down-regulated by infection. Conversely, LM infection of R2 cells did not affect reporter cell stimulation compared with uninfected R2 controls. We characterized a rat monocyte cell line, termed RmW cells. In contrast to LM infected R2 cells that up-regulate MHC class I molecules, RmW cells displayed unchanged MHC class I expression following infection. In line with MHC class I expression, more NK cells produced a higher amount of IFN-γ against infected R2 cells compared with RmW cells. Together, L. monocytogenes infection may variously regulate cellular ligands for NK cells, depending on the cell type infected, affecting the outcome of NK cell responses.